Authentic leadership on widespread organization: as an authentic leader provincial gendarmerie commander's impacts on creativity, organisational identification, leader-member exchange (LMX), and emergence of his staff's potential capabilities - Sercan, Gürcan (2016)
As the world changes, the types of threats and obstacles or dangers are also changing. The security organisations have to adapt this situation by not only supporting themselves with new technologies but also developing their competencies. In Turkey, one of the most significant actors operating to ensure public security is Turkish Gendarmerie Organization. Considering this context, the main objective of this study is to contribute an understanding of a more adequate, effective and efficient model of leadership to the literature for such a widespread organization, which is supposed to adapt in new, unexpected and continuously transforming challenges that organization faces. In this manner, the role of the leader in a widespread organization is what this study calls attention to. This research draws an outline by asking several questions as ‘‘is there difference of the understanding and implementation of authentic leadership between the security sectors and the non-security ones?’’, ‘‘is authentic leadership applicable to Turkish Gendarmerie Organisation as it is adapted to the contexts in civilian sectors?’’ and ‘‘how does authentic leadership have impact on improvement of the personnel?’’. The main standpoint of the research is to reveal if the authentic leadership model, a new leadership model developed in recent decades, is applicable and beneficial for Turkish Gendarmerie Organization. In order to examine this objective, authentic leadership model is analysed according to its basic dimensions; relational transparency, balanced processing of information, his/her ethical moral standards, and also the leader’s self-awareness in addition to other major leadership models have been utilized in such widespread organizations so far. In this research both qualitative and quantitative methodological approaches are used in order to investigate the authentic leadership with these four dimensions abovementioned, and the notions of this models’ implementation. By utilizing the data obtained from the qualitative and quantitative methods, interrelated and interactive relationships of the followers and leader are aimed to be studied.This research presents the empirical results of a survey determining the Authentic Leadership (with its concepts; Transparency, Ethical/Moral and Self-awareness) and its impacts on both leaders and followers investigating creativity, organisational identification, leader-member exchange (LMX) and emergence of potential capabilities. The sample used in the analysis (N=171) was taken from Turkish Gendarmerie Organisation members, both in active duty and retired. The results of the study indicate that Transparency is related with the perception of commanders regarding personnel’s creativity (CPLP). Furthermore, with its all concepts, AL has a positive relationship with the role of leaders in stimulating follower’s creativity (RLSFC). Moreover, the effects of the leader on subordinates’ abilities (EAPLE) are related to Self-awareness. One of the important point is that Ethical/Moral concept of the AL determines the Organisational Identification (OI). The results also identify the positive relationship between LMX and the two concepts of AL, Ethical/Moral and Self-awareness. Overall this research gives a contribution for the Leadership literature and for the understanding of authentic leadership in widespread organizations.